Innovating teacher feedback with writing activities aimed at raising secondary school students’ awareness of collocation errors - Reynolds, Barry Lee; Teng, Mark Feng (Studies in Second Language Learning and Teaching, 2021)
The study examined the types of written corrective feedback given by second language writing teachers on Taiwanese secondary school students’ collocation errors. First, the written corrective feedback that teachers provided on learners’ word choice errors was examined to uncover the types of feedback provided. Then, analysis focused on verb–noun collocations to draw attention to how students had been receiving different types of written corrective feedback from teachers on a single collocation error type. Results showed that some sentences tagged as including word choice errors only contained rule-based errors. Furthermore, for verb-noun collocation errors, teachers chose to provide indirect and direct feedback almost equally at the expense of metalinguistic feedback. Based on the results, we suggested options for second language writing teachers when providing feedback on word choice errors.